Effect of Composition, Temperature, and Pressure on the Viscosities and Densities of Three Diesel Fuels - Rowane, Aaron J.; Mahesh Babu, Vikrant; Rokni, Houman B.; Moore, Joshua D.; Gavaises, Manolis; Wensing, Michael; Gupta, Ashutosh; McHugh, Mark A. (Journal of Chemical and Engineering Data, 2019)
In this work, a rolling-ball viscometer/densimeter is used to measure high-pressure, high-temperature (HPHT) density and viscosity data from 298.2 to 532.6 K and pressures up to 300.0 MPa for three different diesel fuels. The densities and viscosities have combined expanded uncertainties of 0.6 and 2.5%, respectively, with a coverage factor, k = 2. Two of the diesels contain either a larger paraffinic or a larger aromatic content relative to the others and are standard engine test fuels. The third is an ultralow sulfur diesel that resembles an unfinished commercial diesel. Detailed compositional information is also reported for each diesel that provides a basis for interpreting the impact of composition on density and viscosity at high pressures. Both density and viscosity data are correlated to Tait-type equations with uncertainties of 0.6 and 4.0%, respectively. The Tait equations provide a facile means to compare observed differences in the density-pressure and viscosity-pressure profiles of the three different diesels. Density data are modeled with the perturbed-chain statistical associating fluid theory (PC-SAFT) equation of state (EoS) with pure component parameters calculated representing diesel as a single, pseudo-component only requiring average molecular weight (Mave) and hydrogen-to-carbon ratio (RH/C) as inputs. Viscosity data are modeled reasonably well using entropy scaling coupled with the PC-SAFT EoS and information on the diesel Mave and RH/C. The HPHT viscosity data are also modeled reasonably well with free volume theory with model parameters correlated to Mave and RH/C
CRIS-Team Scopus Importer:2019-11-19